Reducing juvenile justice involvement through a childhood truancy intervention - Blackmon, Bret James (2014)
This study employed a mixed methods design to evaluate an elementary school truancy intervention in terms of reducing rates of juvenile delinquency over six years. Few (n = 11) participants became involved in the formal justice system, so the intervention’s effectiveness was measured by re-referrals for continued truancy. The regression discontinuity design was used to compare the intervention group to the comparison group. The intervention group received intensive case management and the comparison group received a warning letter. A regression discontinuity design using multivariate logistic regression indicated that the intervention did not reduce the likelihood of subsequent re-referrals, and the null hypothesis was retained. The qualitative portion of the study employed a grounded theory research design to examine the perspectives of the truancy intervention’s case managers. A core category emerged that the case manager was the agent of change. Hence, this author postulated that the participants’ long-term success was based on the case managers’ commitment to the participant’s family, the case managers’ ability to help the family build a collaborative support network, and the case managers’ support in helping the family to overcome treatment barriers. Implications for social work policy, practice, and future research are presented